Dural arteriovenous fistulas as a relative contraindication for lumbar puncture: brief report and literature review. (4th July 2022) - Ghorbani, Mohammad; Azar, Maziar; Shojaei, Hamidreza; Griessenauer, Christoph J.; DeHoff, Grace; Khosravi, Darya
Abstract: We report three patients who deteriorated after lumbar puncture (LP). Two patients were later found to have type іі (a + b) dural arteriovenous fistulas (DAVF) with high flow retrograde venous drainage on cerebral angiography. The third had a type II (a) DAVF. All patients recovered at least partially after DAVF treatment. In patients with signs and symptoms of increased intracranial pressure (ICP) but no evidence of focal mass lesion on cranial imaging, we suggest an evaluation for a DAVF before performing an LP.